2015
DOI: 10.1016/j.tice.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Relative distribution of gastrin-, CCK-8-, NPY- and CGRP-immunoreactive cells in the digestive tract of dorado (Salminus brasiliensis)

Abstract: The endocrine cells (ECs) of the gastrointestinal mucosa form the largest endocrine system in the body, not only in terms of cell numbers but also in terms of the different produced substances. Data describing the association between the relative distributions of the peptide-specific ECs in relation to feeding habits can be useful tools that enable the creation of a general expected pattern of EC distribution. We aimed to investigate the distribution of ECs immunoreactive for the peptides gastrin (GAS), cholec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…niloticus (Pereira et al, ) and as well as carnivorous S . brasiliensis (Pereira et al, ) showed larger number of NPY+ cells in the midgut segment, near by the stomach. NPY+ ECs in I .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…niloticus (Pereira et al, ) and as well as carnivorous S . brasiliensis (Pereira et al, ) showed larger number of NPY+ cells in the midgut segment, near by the stomach. NPY+ ECs in I .…”
Section: Discussionmentioning
confidence: 98%
“…The polyclonal antibodies used herein were selected according to their accuracy at recognizing peptide hormones CCK‐8 and NPY, produced by intestinal ECs in other fishes, including Nile tilapia ( Oreochromis niloticus ; Pereira et al, ), dorado ( Salminus brasiliensis ; Pereira et al, ), South American catfish ( Rhamdia quelen ; Hernández et al, ), and pejerrey ( Odontesthes bonariensis ; Vigliano et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Since then, NPY has been one of the most studied appetite-regulating hormones in fish. It has been cloned and/or shown to regulate feeding in several groups, including Characiformes (Pereira et al, 2015), Cypriniformes [(e.g., goldfish, zebrafish (Yokobori et al, 2012), blunt snout bream Megalobrama amblycephala (Xu et al, 2016), grass carp Ctenopharyngodon idellus (Jin et al, 2015), Jian carp ( Cyprinus carpio ) (Tang et al, 2014), Ya fish (Wei et al, 2014)], Gadiformes (Atlantic cod Kortner et al, 2011; Tuziak et al, 2014); Gonorynchiformes (milkfish Chanos chanos , Lin et al, 2016); Perciformes (yellowtail Seriola quinqueradiata Hosomi et al, 2014, Astatotilapia burtoni Grone et al, 2012, cunner Tautogolabrus adspersus Babichuk and Volkoff, 2013, orange-spotted grouper Epinephelus coioides Tang et al, 2013, sea bass Leal et al, 2013, mandarin fish, Siniperca chuatsi Sun et al, 2014, cobia Rachycentron canadum Van Nguyen et al, 2013, gourami Trichogaster pectoralis Boonanuntanasarn et al, 2012); Pleuronectiformes (olive flounder Wang et al, 2015, winter flounder MacDonald and Volkoff, 2009a, Brazilian flounder Paralichthys orbignyanus Campos et al, 2012), Salmoniformes (e.g., rainbow trout Oncorhynchus mykiss Aldegunde and Mancebo, 2006, Atlantic salmon Valen et al, 2011; Kim et al, 2015), Siluriformes (channel catfish, Peterson et al, 2012; Schroeter et al, 2015); Tetraodontiformes (tiger puffer Takifugu rubripes Kamijo et al, 2011) as well as elasmobranchs [(e.g., winter skate Leucoraja ocellata , Rajiforme (MacDonald and Volkoff, 2009b) and spotted catshark ( Scyliorhinus canicula , Carcharhiniforme) Mulley et al, 2014)] and holocephalans (elephant fish Chimaeriformes; Larsson et al, 2009). The majority of these studies indicate that NPY has a widespread distribution and is present in both brain and intestinal tract, that it acts as an orexigenic factor and that its expression is affected by feeding and fasting.…”
Section: Hormones Involved In Food Intakementioning
confidence: 99%
“…The first direct evidence of the actions of CCK on feeding was provided by injections in goldfish (Himick and Peter, 1994), followed by cloning of goldfish CCK cDNA (Peyon et al, 1998) and the demonstration of periprandial variations in CCK mRNA expression levels (Peyon et al, 1999). Subsequently, a number of studies have characterized CCK in several fish, including other Cypriniformes (e.g., common carp Zhong et al, 2013; zebrafish Koven and Schulte, 2012; Tian et al, 2015; grass carp; blunt snout bream Ping et al, 2013; Ji et al, 2015), Characiformes (e.g., cavefish Wall and Volkoff, 2013, dourado Pereira et al, 2015; Volkoff et al, 2016, thin dogfish Oligosarcus hepsetus Vieira-Lopes et al, 2013, pirapitinga Volkoff, 2015a, red-bellied piranha Volkoff, 2014a, pacu Volkoff et al, 2017), Salmoniformes (e.g., Atlantic salmon Valen et al, 2011), Gadiformes (Atlantic cod Tillner et al, 2013), Perciformes [e.g., yellowtail (Furutani et al, 2013; Hosomi et al, 2014); Astatotilapia burtoni (Grone et al, 2012); cunner (Babichuk and Volkoff, 2013; Hayes and Volkoff, 2014); sea bass (Tillner et al, 2014); yellow croaker ( Larimichthys crocea ) (Cai et al, 2015); white sea bream, Diplodus sargus (Micale et al, 2012, 2014)], Pleuronectiformes (e.g., winter flounder (MacDonald and Volkoff, 2009a), Atlantic halibut Kamisaka et al, 2001, olive flounder Kurokawa et al, 2000) and Siluriformes (channel catfish Peterson et al, 2012). …”
Section: Hormones Involved In Food Intakementioning
confidence: 99%
“…Because of the difficulty of obtaining antibodies to A. bimaculatus against the proteins studied, and because of these proteins are conserved in the phylogenetic scale (Buddington and Krogdahl, 2004;Nelson and Sheridan, 2006;Daza et al, 2012;Pereira et al, 2015), we used polyclonal antisera produced in mammals against 5-HT, SST and GAS. Several earlier studies used antibodies produced in mammals and obtained consistent results in fishes, proving the affinity of the antibodies (e.g., Ku et al, 2004;Hernández et al, 2012;Vieira-Lopes et al, 2013).…”
Section: Histochemical and Immunohistochemical Analysismentioning
confidence: 99%